2012
DOI: 10.1007/s00404-012-2593-y
|View full text |Cite
|
Sign up to set email alerts
|

Tranexamic acid for the prevention of postpartum hemorrhage after cesarean section: a double-blind randomization trial

Abstract: Treatment with TXA is effective in reducing blood loss in patients undergoing CS. Although the study was not adequately powered to address safety issues, the observed side effects were mild and transient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
134
2
10

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(156 citation statements)
references
References 17 publications
10
134
2
10
Order By: Relevance
“…Its efficacy, in reducing blood loss and transfusion requirements, in both these settings has been confirmed. [60][61][62] For speed and simplicity we use a For personal use only. on April 29, 2019.…”
Section: Tranexamic Acidmentioning
confidence: 99%
“…Its efficacy, in reducing blood loss and transfusion requirements, in both these settings has been confirmed. [60][61][62] For speed and simplicity we use a For personal use only. on April 29, 2019.…”
Section: Tranexamic Acidmentioning
confidence: 99%
“…The blood loss from the end of CS to 2 hours post delivery of 42.75±40.45 ml in the TXA group versus 73.98±77.09 ml in the control group (P=0.001) was also comparable [20] . The blood loss in the two periods was also significantly reduced in the TXA group according to Xu J et al [21] and Mayur G et al [22] .…”
Section: Discussionmentioning
confidence: 88%
“…Xu et al [33] tried intravenous injection of 10 mg/kg TXA immediately before CS and found blood loss in the period between the end of CS and 2 h postpartum was significantly lower in the TXA group than in the control group and PP hemorrhage stopped in 75.6 % of controls and in 92% in TXA group with significant difference in favor of TXA.…”
Section: Discussionmentioning
confidence: 99%